2013
DOI: 10.1182/blood-2012-12-475897
|View full text |Cite
|
Sign up to set email alerts
|

The Rac activator DOCK2 regulates natural killer cell–mediated cytotoxicity in mice through the lytic synapse formation

Abstract: Key Points• DOCK2-deficienct NK cells fail to effectively kill leukemia cells in vitro and major histocompatibility complex class I-deficient bone marrow cells in vivo.• Activating NK receptor-mediated Rac activation and the lytic synapse formation are severely impaired in DOCK2-deficient NK cells.Natural killer (NK) cells play an important role in protective immunity against viral infection and tumor progression, but they also contribute to rejection of bone marrow grafts via contact-dependent cytotoxicity. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 43 publications
2
31
0
Order By: Relevance
“…Altogether, these data demonstrate that DOCK2 serves an essential role in NK and NKT cell biology, consistent with similar observations in mice 17,18 .…”
Section: Resultssupporting
confidence: 90%
“…Altogether, these data demonstrate that DOCK2 serves an essential role in NK and NKT cell biology, consistent with similar observations in mice 17,18 .…”
Section: Resultssupporting
confidence: 90%
“…Additionally, we found that fMLFinduced phosphorylations of ERK, Akt, and p38, which are closely associated with Rac activation in neutrophils (3,6,7), are severely impaired in DKO neutrophils. The importance of DOCK2 and DOCK5 could be extended to human neutrophils, because fMLF-induced Rac activation, chemotaxis, and ROS production were almost completely lost when human peripheral blood neutrophils were treated with CPYPP (25)(26)(27). Our results thus identify DOCK5 as a Rac GEF that acts additively with DOCK2 in the GPCR-mediated signaling pathway in humans and mice.…”
Section: Discussionmentioning
confidence: 64%
“…To examine whether the role of DOCK2 and DOCK5 could be extended to human neutrophils, we used CPYPP, a small-molecule inhibitor that binds to the DHR-2 domain of DOCK-A subfamily members and inhibits their Rac GEF activity (25)(26)(27). As expected, treatment of human peripheral blood neutrophils with CPYPP at 100 mM reduced fMLF-induced Rac2 activation to 22.5% of the vehicle (DMSO)-treated samples (Fig.…”
Section: A Small-molecule Inhibitor Of Dock2/dock5 Suppresses Human Nmentioning
confidence: 99%
See 1 more Smart Citation
“…2). A recent study from Fukui and colleagues demonstrated that PIP 3 also recruits Dock2 to the NK cell IS[83], suggesting that this pathway is conserved among all lymphocytes.…”
Section: Synaptic Actin Remodelingmentioning
confidence: 99%